Integrated Inflammatory, Thrombo-Inflammatory, Redox and Soluble IFNAR2 Profiling During Hospitalization for COVID-19: An Exploratory Observational Cohort Study - Álvaro Martínez Mesa; Eva Cabrera César; María García-Fernandez; Pablo Zamorano-González; María Mercedes Segura Romero; Javier López García; Elisa Martín-Montañez; Óscar Fernández; Jose Luis Velasco Garrido (Journal of Clinical Medicine, 2026)
Background: Severe COVID-19 reflects a multi-layered host response with systemic inflammation, thrombo-inflammation, tissue damage, oxidative stress and altered antiviral interferon biology. We performed an integrated exploratory analysis of first-wave hospitalized patients to identify biomarker patterns associated with adverse clinical evolution during established admission. Methods: We analyzed 60 hospitalized COVID-19 patients and 18 healthy controls for soluble IFNAR2 (sIFNAR2) comparison. Biomarker samples were obtained during hospitalization, approximately seven days after symptom onset. Outcomes were final clinical status, severe respiratory involvement, post-sampling clinical worsening and death. Analyses included non-parametric testing, false-discovery-rate adjustment, effect-size estimation, exploratory ROC curves, parsimonious regression, penalized internal validation, composite scores and molecular-structure analyses. Results: Final status was favorable outcome in 31 patients, severe non-fatal disease in 22 and death in 7. sIFNAR2 was higher in patients than in healthy controls and highest among non-survivors, but did not distinguish favorably from severe non-fatal disease. The most consistent severity-associated signals were IL-6, D-dimer, total thiols, IL-10, LDH, ferritin, leukocytes and IL-1RA. D-dimer, IL-6 and ferritin yielded the largest exploratory univariable AUCs for severe respiratory involvement, whereas ferritin, IL-10, IL-1RA and sIFNAR2 predominated in event-limited mortality analyses, which were based on only seven deaths. Composite multi-axis scores and PLS-DA were tools requiring external validation. Conclusions: Biomarker patterns during admission were associated with adverse evolution. Conventional markers remained the most practical signals, while cytokines, redox markers and sIFNAR2 provided complementary biological information. sIFNAR2 should be interpreted as an exploratory complementary marker of the interferon receptor axis, mainly linked to mortality, not as a stand-alone clinical test or functional measure of IFNAR signaling.